If (frac{sqrt{2} + sqrt{3}}{sqrt{3}}) is simplified as m + n(sqrt{6}), find the value of (m + n)

**A.**

(frac{1}{3})**B.**

(frac{2}{3})**C.**

1(frac{1}{3})**D.**

1(frac{2}{3})

##### Correct Answer: Option C

##### Explanation

(frac{sqrt{2} + sqrt{3}}{sqrt{3}}) = (frac{sqrt{2} + sqrt{3}}{sqrt{3}}) x (frac{sqrt{3}}{sqrt{3}})

= (frac{sqrt{2} times sqrt{3} + sqrt{3} times sqrt{3}}{sqrt{3} times sqrt{3}})

= (frac{sqrt{6} + 3}{3})

= (frac{3 + sqrt{6}}{3})

= Hence, (m + n) = 1 + (frac{1}{3})

= 1(frac{1}{3})